MAPPinfo, mapping quality of health information: study protocol for a validation study of an assessment instrument. Issue 11 (3rd November 2020) - Kasper, Jürgen; Lühnen, Julia; Hinneburg, Jana; Siebenhofer, Andrea; Posch, Nicole; Berger-Höger, Birte; Grafe, Alexander; Keppler, Jan; Steckelberg, A
Abstract : Introduction: Health information is a prerequisite of informed decision-making. Criteria for development, content and presentation have recently been published in a corresponding guideline. Within a systematic search, 27 relevant checklists were identified, none of them, however, complying with the guideline or providing reasonably operationalised measurement items. Therefore, a draft of a checklist with 19 criteria was drafted. The current study aims at developing and validating this measure of quality. Methods and analysis: The validation design consists of five single studies to be conducted at the University of Halle-Wittenberg/Germany and Graz/Austria. (1) Achieving content validity through expert reviews of the first draft, (2) achieving feasibility using 'think aloud' in piloting with untrained users, (3) pretesting the instrument applied to health information materials without use of secondary sources: determining inter-rater reliability and criterion validity, (4) determining construct validity using information on proceedings and methods in the development process provided by the developers and (5) determining divergent validity in comparison with the Ensuring Quality Information for Patients (EQUIP) (expanded) Scale. The substudies will use varying samples of experts, students and developers and will apply the instrument to materials of various domains. Sample sizes will be adjusted to the particular research designs and questions. Analyses will employ qualitative methods, such as content analyses and discourse within the expert panel, and correlation-based methods both for determining inter-rater reliability and validity. Ethics and dissemination: The project is approved by the ethics committee of the Martin Luther University Halle-Wittenberg (approval number: 2019 115). Results will be published, and the instrument made accessible on public health platforms. It is meant to become a certification standard. MAPPinfo can be used as a screening instrument without training or secondary sources. Although developed in the German language, the instrument will be applicable also in other languages. Trial registration number: AsPredected22546; date of registration: 24 July 2019. Protocol version: July 2020.